La Cambre : Yearbook 2018. - La Cambre; Pantanacce, Marie; Hennaut, Benoît (Bruxelles : La Cambre, 2019)
Abitbol, Stéphane ; Abiteboul, Emmanuel ; Anselot, David ; Ayive, Alexandre ; Bakkali, Camille ; Baraka, Sarah ; Beaumont, Marine ; Bechari, Romy ; Bridi, Chirine Ben Omar ; Benazet, Estelle ; Bergerot, Fanny ; Bollette, Elena ; Bonvalot, Jérôme ; Bourez, Cyril ; [et al.]
École Nationale Supérieur des Arts Visuels
boek